The dirt cure : a whole food, whole planet guide to growing healthy kids in a processed world - Shetreat-Klein, Maya (New York : Atria Books, 2016)
An integrative pediatric neurologist reveals harmful ingredients in children's food and their potential for injuring developing brains and bodies, outlining a nutritional plan for promoting health through informed, child-friendly food choices.
Keywords: Children -- Nutrition; Diet therapy for children; Children -- Health and hygiene; Children -- Nutrition; Diet therapy; Children -- Health and hygiene